Does arteriovenous fistula operation cause neuropathy in upper extremity? An EMG study. (Annals of Medical Research, 2022)
Aim: Neuron function is impaired in uremic patients and peripheral neuropathy occurs in 60-80% of patients with end-stage renal disease. However, the effects of arteriovenous fistula intervention on the nerve functions in those are uncertain. The purpose of this study is to weigh the effects of arteriovenous fistula intervention on the nerve functions by using electromyography among patients who have end-stage renal disease.Materials and Methods: Forty-three renal insufficiency patients on dialysis, living in Somalia, who had undergone arteriovenous fistula operation, were included in the present prospective study. Demographic characteristics were recorded. The electromyographic measures (both motor and sensorial) of median, ulnar, radial nerve on the operated side arm were assessed. Tibial, peroneal and sural nerve electromyographic measures were also evaluated. After the arteriovenous fistula operation, the electromyographic measures were again assessed to determine the effects of arteriovenous fistula intervention on the nerve functions.Results: The mean age of patients was 56 ± 17 years and 56.3% of them were male. 88% of the recruited patients underwent radiocephalic fistula operation while in the remaining 12% type of the fistula was brachiocephalic. Between the pre and the post-operative electromyographic measures, there were not any significant changes except tibial nerve motor distal latency. The mean tibial nerve motor distal latency decreased with operation from 6.59±1.39 ms to 6.17±1.18 ms (p =0.038). Upper extremity motor and sensory nerve amplitudes, except ulnar sensory nerve amplitude, were found to have a non-significant decrease trend after surgery. Lower extremity motor and sensory nerve amplitudes non-significantly increased after surgery.Conclusions: This is the first prospective study to investigate the relationship of nerve functions with arteriovenous fistula operation by monitoring the electromyographic measures among end-stage renal disease patients. The present results demonstrated that arteriovenous fistula operation did not have unfavorable effects on nerve functions in the adjacent operation side. Further studies are needed with a larger sample size to verify this issue.
Keywords: Neuropathy; electromyography(EMG); arteriovenous fistula